Inhibition studies on a panel of human carbonic anhydrases with N1-substituted secondary sulfonamides incorporating thiazolinone or imidazolone-indole tails - Awadallah, Fadi M. (J Enzyme Inhib Med Chem, 2018)
Being the primary sulfonamide among the most efficient zinc binding group (ZBG) to design inhibitors for the metallo-enzymes carbonic anhydrases (CA, EC 4.2.1.1), herein, we propose an investigation on four physiologically important human (h) CAs (hCA I, II, IV, and IX) with N(1)-substituted secondary sulfonamides incorporating thiazolinone or imidazolone-indole tails. The effect of the functionalisation of the sulfonamide group with five different substitution patterns, namely acetyl, pyridine, thiazole, pyrimidine, and carbamimidoyl, was evaluated in relation to the inhibition profile of the corresponding primary sulfonamide analogues. With most of these latter being nanomolar inhibitors of all four considered isoforms, a totally counterproductive effect on the inhibition potency can be ascribed to N(1)-functionalisations of the ZBG primary sulfonamide structure with pyridine, thiazole, and pyrimidine moieties. On the other hand, incorporation of less hindered groups, such as sulfonylacetamides and sulfonylguanidines, maintained a certain degree of activity dependent on the tailing moiety, with K(I)s spanning in the low micromolar range.